(untitled) (Conversatoria Linguistica, 2019)
The article seeks to present the semantic abilities of a woman with mod-erate intellectual disability in defining the concepts of happiness, suffering, childhood, illness, disability, and fashion. The principal objective was to reconstruct the structure of the foregoing concepts and to show the ways of categorizing them. The study seeks to answer the question whether the tested woman actually uses a restricted code (in terms of B. Bernstein’s conception) because her linguistic abilities are developed enough for her to be able to easily include in the constructed definitions the important information preserved in language, supported by observations, experiences, and reflection for her abilities.